2008
DOI: 10.1186/1757-1626-1-284
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis of bronchogenic carcinoma to the 5thmetacarpal bone: a case report

Abstract: Background: Metastatic lesions to the hand are very rare and represent 0.1% of all osseous metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Tzaveas et al have reported metastasis of bronchogenic lung cancer to the 5th metacarpal [6]. The bronchogenic adenocarcinoma usually erodes the pulmonary veins and thus access to systemic circulation and consequently shows wide spread metastasis [6]. Our case is an unusual presentation of adenocarcinoma lung with the diagnostic difficulties due to non specific presentation and by absence of an obvious mass lesion in chest X ray.…”
Section: Case Reportmentioning
confidence: 73%
See 1 more Smart Citation
“…Tzaveas et al have reported metastasis of bronchogenic lung cancer to the 5th metacarpal [6]. The bronchogenic adenocarcinoma usually erodes the pulmonary veins and thus access to systemic circulation and consequently shows wide spread metastasis [6]. Our case is an unusual presentation of adenocarcinoma lung with the diagnostic difficulties due to non specific presentation and by absence of an obvious mass lesion in chest X ray.…”
Section: Case Reportmentioning
confidence: 73%
“…Bone metastasis usually occurs late in the course of the disease, but in some patients it may be the first manifestation of lung cancer [5]. Tzaveas et al have reported metastasis of bronchogenic lung cancer to the 5th metacarpal [6]. The bronchogenic adenocarcinoma usually erodes the pulmonary veins and thus access to systemic circulation and consequently shows wide spread metastasis [6].…”
Section: Case Reportmentioning
confidence: 99%
“…The localization in metacarpal and the proximal phalanges is rarer. And it is extremely rare in carpal bones [7].…”
Section: Discussionmentioning
confidence: 99%
“…This clinical presentation may confuse other diagnoses such as hand infection, septic arthritis or osteomyelitis, rheumatic monoarthritis, algoneurodystrophy, tenosynovitis and gout disease [5] [6] [7].…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic carcinoma to the digits of the hands is exceedingly rare, although it has been reported. One such case reported metastasis of bronchogenic lung cancer to the fifth metacarpal 3 . We report a case of a 59-year-old male patient who presented with urothelial carcinoma of the bladder without evidence of metastatic disease on whole-body imaging.…”
Section: Introductionmentioning
confidence: 99%